Espaços da alegria: imagens Guarani e Kaiowá (ou os povos indígenas contra o ódio do Estado brasileiro) - Juliana Grasiéli Bueno Mota; Jones Dari Goettert; Valentim Pires (Confins)
Kaiowá and Guarani peoples create spaces of joy as a counterpoint to hatred against indigenous peoples. “Choças Caiuá”, hands weaving a caraguatá hammock, a bread oven became into a toyhouse and a story in a neo-Pentecostal church are expressed here as spaces of affection and hapiness, making the present moments of yesterday and today as experiences under that becoming. An endeavor, specifically, to make the Geography filled of a multiplicity, that also makes laughs of life, of struggle and of resistance. Where are the spaces of indigenous joy? This is the goal here.